2012
DOI: 10.1002/pon.3078
|View full text |Cite
|
Sign up to set email alerts
|

Being within or being between? The cultural context of Arab women's experience of coping with breast cancer in Israel

Abstract: Healthcare professionals should be aware of the unique implications of cancer in the context of the traditional Arab culture intertwined with modernization processes. This context calls for interventions that consider the understandings depicted in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 47 publications
7
42
0
Order By: Relevance
“…However, Muslim women wearing the hijab faced additional challenges of tangible discrimination and abuse in employment and public spaces. This supports previous findings highlighting the unique forms of discrimination that Muslim immigrant women face at the intersection of religion, race and gender [39, 40]. The stereotypical beliefs about Muslims being sympathetic to terrorism and hence potential threats to national security as well as the hijab being viewed as a symbol of woman’s subservience to male oppression, and a sign of docility and powerlessness can contribute to Muslim women’s feeling of alienation and exclusion.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, Muslim women wearing the hijab faced additional challenges of tangible discrimination and abuse in employment and public spaces. This supports previous findings highlighting the unique forms of discrimination that Muslim immigrant women face at the intersection of religion, race and gender [39, 40]. The stereotypical beliefs about Muslims being sympathetic to terrorism and hence potential threats to national security as well as the hijab being viewed as a symbol of woman’s subservience to male oppression, and a sign of docility and powerlessness can contribute to Muslim women’s feeling of alienation and exclusion.…”
Section: Discussionsupporting
confidence: 88%
“…We found that religious and cultural beliefs affected women’s views on cancer (seeing it as a “death sentence”), willingness to disclose family history of cancer, emphasis on treatment rather than prevention, which has been reported in other studies [4046], and cultural taboo surrounding female sexuality and sexual activity. Most cases of cancer that women narrated ended in demise and the occurrence of survival was almost nominal.…”
Section: Discussionsupporting
confidence: 61%
“…The cultural expectations of marriage, childbearing, and nurturing relates to the significance of the breast for women (Goldblatt, Cohen, Azaiza, & Manassa, 2012) and could be a source of anxiety for a younger woman with breast cancer, especially those who were not married or were childless at the time of diagnosis. Perhaps the infusion of foreign culture where marriage and childbearing are not a priority could minimize the level of anxiety where such cultural expectations predominate.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that younger women often demonstrate poorer psychosocial adjustment during and following breast cancer treatment (Ahmad, Fergus, & McCarthy, 2015; and express an unmet need of professional and emotional support when communicating their cancer diagnosis to their children . However, this may also reflect the perception of the woman as the pillar of the home, strong and available for family members to the detriment of her own needs and difficulties, as shown by Goldblatt, Cohenz, Azaiza, and Manassa (2013) when exploring how Arabic women living in Israel experience and cope with breast cancer.…”
Section: Staying In Controlmentioning
confidence: 99%